Fatigue Life Analysis of 2.5MW Wind Turbine Gearbox based on Romax - Wu Jianwei; Chen Huanguo; Chen Wenhua; Chen Te; Pan Xiaodong (Jixie chuandong)
In order to develop new products of MW wind turbine gearbox,improve the design efficiency and calculation accuracy,and reduce product development risks and costs,the 2. 5 MW power-split wind turbine gearbox transmission system model is set up based on Romax Designer software,and the result of power split,bearing life,the strength of gear is analyzed and the potential weakness of the gear transmission system is researched,the theory basis for further optimization design is provided.